IbM PEMBELAJARAN RAMAH ANAK BAGI ORANG TUA DAN GURU TK-PAUD DI KEC. GODONG KABUPATEN GROBOGAN - Ismatul Khasanah; Aries Tika Damayani; Qoriati Mushafanah; Venty . (Universitas PGRI Semarang, 2014)
Abstract Children are a gift from the Almighty so that every person who shall be blessed with a child to love , guide , provide the best education and welfare efforts in accordance with the ability of the child's parents have since also the future of the family role of the teacher is also a central factor that will deliver learners . Analysis of the situation described above , we can identify some partner issues , among others : 1 ) Potential - kindergarten early childhood teachers in the district are still in need of assistance Godong in improving skills in educating children . So it takes a child-friendly learning activities for parents to students to be smart and love to learn . 2 ) lack of skills in using instructional media in AUD. 3 ) Lack of storytelling skills / storytelling for children . Storytelling is a skill that must be honed so often the message will be delivered at the time told me to be accepted by the students . Ape is as a medium for membelajarkan children to play and learn fun activities and messages to be delivered to be well received by the students . The role of the teacher is also a central factor that will lead learners . Skills necessary to educate very very well to the teaching and learning activities for children early childhood / kindergarten , educators are required to understand the child's character and desire not the desire of parents . Keywords :IbM, Friendly teaching children, parents and teachers